Helmintofauna associativa à anfíbios da Ilha Anchieta, litoral norte do estado de São Paulo, Brasil - Aguiar, Aline [UNESP] (2013)
The amphibians use a variety of microhabitats, relationship with the various reproductive modes, life style and parasites that these animals presented. The parasites are indicatives about a lot of biological aspects of yours hosts, including feeding, use of habitat and phylogeny. They also may be good indicators about status of environmental quality. The Anchieta Island, state park in Atlantic Rain Forest area, is very interesting for biological studies because insular dynamics and geographical isolation. The aim of this study was to evaluate the helminth fauna of 195 amphibians from Anchieta Island representing 14 species, Flectonotus fissilis (n = 18), Haddadus binotatus (n = 9), Ischnocnema bolbodactyla (n = 4), Ischnocnema parva (n = 20), Rhinella ornata (n = 20), Dendrophryniscus brevipollicatus (n = 3), Hypsiboas albomarginatus (n = 18), Scinax hayii (n = 23), Hylodes asper (n = 2), Hylodes phyllodes (n = 3), Leptodactylus cf. marmoratus (n = 42), Leptodactylus latrans (n = 4), Chiasmocleis carvalhoi (n = 26), and Myersiella microps (n = 3). They were necropsied to examine for helminth parasites. We identified at least 14 helminths species in the component communities of anurans: 12 nematodes species (Falcaustra mascula, Oxyascaris oxyascaris, Oswaldocruzia sp., Rhabdias sp., Physaloptera sp., Aplectana crucifer, Aplectana pintoi, Aplectana sp., Cosmocerca brasiliense, Cosmocerca parva, Cosmocerca travassosi, and Cosmocerca sp.), one cestode species (Cylindrotaenia cf. americana), and one species of Acanthocephala (cystacanths). This study presents a revision about these helminth species with the related hosts to date; the helminth fauna associated to these host species; and the similarity about infracommunities of some amphibian species, showing habitat can influence on composition and abundance of parasite community